A Stability Indicating UPLC Method for the Determination of Levofloxacin Hemihydrate in Pharmaceutical Dosage Form: Application to Pharmaceutical Analysis. (19th June 2013) - Dabhi, Batuk; Parmar, Bhavesh; Patel, Nitish; Jadeja, Yashwantsinh; Patel, Madhavi; Jebaliya, Hetal; Karia, Denish; Shah, A. K.
Abstract : A reliable and sensitive isocratic stability indicating RP-UPLC method has been developed and validated for quantitative analysis and content uniformity study of levofloxacin hemihydrate in tablets. An isocratic method for analysis of levofloxacin hemihydrate was archived on ACQUITY UPLC BEH C18 (100*2.1) mm particle size 1.7 μ columns within shorter runtime of 4 min with a flow rate of 0.400 mL/min and using a photodiode array detector to monitor the eluate at 294 nm. The mobile phase consisted of acetonitrile-buffer (23 : 77 v/v), (buffer: 20 mM K2 HPO4 + 1 mL triethylamine in 1 L water, p H = 2.50 by orthophosphoric acid). Response was a liner function of drug concentration in the range of 0.5–80 μ g/mL (r 2 = 0.999 ) with a limit of detection and quantification of 0.1 and 0.5 μ g/mL, respectively. Accuracy (recovery) was between 99.77% and 101.55%. The drug was subjected to oxidation, hydrolysis, photolysis, and thermal degradation. Degradation products resulting from the stress studies did not interfere with the detection of levofloxacin hemihydrate, and the assay is stability indicating.